INFORMATION TECHNOLOGY IMPLEMENTATIONS AND LIMITATIONS IN MEDICAL RESEARCH - Maciejewski, Marcin (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2019)
The article presents an overview of common uses of information technology in medicine and medical diagnostics, also pointing out major obstacles in the process of introducing information technology in the fields above . Information technology tools widely used in medicine include but are not limited to databases, decision algorithms and data processing and mining methods. Major obstacles include heterogeneity of medical data, their complexity and free text descriptions of procedures, diagnoses and interpretations of test results.